1984
DOI: 10.1037/0736-9735.1.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in 2- and 3-years-olds: Mother-child relations, peer relations, and peer play.

Abstract: This paper examines the different behavior patterns utilized by boys and girls as they form peer relationships and engage in peer play; the nature of their relations with their mothers is also reported. Girls manifested more intense involvement with their mothers, engaged in less peer play than boys, showed lower mood, lower levels of play, less direct aggression, and more controlling play with peers. Furthermore, their mothers handled their requests for contact and aggressive behavior differently than did mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Specifically, the literature in gender differences tends to support the general view that females display higher levels of social interest, are better at decoding emotional expressions, and are more invested in social relationships than are males (Gilligan, 1982; Golombok & Fivush, 1994; Halpern, 2000; Lovas, 2005; Maccoby, 1990). Traditional gender role prescriptions also characterize women as more affiliative and interpersonally sensitive, and feminine stereotyped activities tend to emphasize collaborative behaviors and foster social proximity (Caldera, Huston, & O’Brien, 1989; Leaper, 2002; Maccoby, 1988; Ruble et al, 2006); development in girls is usually also associated with higher levels of emotional closeness to significant others (Chodorow, 1978; Clarke-Stewart & Hevey, 1981; Ley & Koepke, 1982; Olesker, 1984, 1990; Robinson & Biringen, 1995). …”
Section: Dyadic Emotional Availability and Child Gendermentioning
confidence: 99%
“…Specifically, the literature in gender differences tends to support the general view that females display higher levels of social interest, are better at decoding emotional expressions, and are more invested in social relationships than are males (Gilligan, 1982; Golombok & Fivush, 1994; Halpern, 2000; Lovas, 2005; Maccoby, 1990). Traditional gender role prescriptions also characterize women as more affiliative and interpersonally sensitive, and feminine stereotyped activities tend to emphasize collaborative behaviors and foster social proximity (Caldera, Huston, & O’Brien, 1989; Leaper, 2002; Maccoby, 1988; Ruble et al, 2006); development in girls is usually also associated with higher levels of emotional closeness to significant others (Chodorow, 1978; Clarke-Stewart & Hevey, 1981; Ley & Koepke, 1982; Olesker, 1984, 1990; Robinson & Biringen, 1995). …”
Section: Dyadic Emotional Availability and Child Gendermentioning
confidence: 99%
“…Specifically, the literature in gender differences tends to support the general view that females display higher levels of social interest, are better at understanding emotional expressions, and are more invested in interpersonal strategies that maintain and repair social relationships than are males (Gilligan, 1982;Golombok & Fivush, 1994;Halpern, 2000;Lovas, 2005;Maccoby, 1990). Traditional gender role prescriptions also characterize women as more affiliative and interpersonally sensitive, and stereotypically feminine activities tend to emphasize collaborative behaviors and foster proximity (Caldera, Huston, & O'Brien, 1989;Leaper, 2002;Maccoby, 1988;Ruble, 1988); development in girls is usually associated with lower levels of autonomy and higher levels of emotional closeness to significant others (Chodorow, 1978;Clarke-Stewart & Hevey, 1981;Ley & Koepke, 1982;Olesker, 1984Olesker, , 1990Robinson & Biringen, 1995). Perhaps more accurately reflective of fact than stereotype, the extant empirical literature on measures of EA and gender is mixed.…”
Section: Dyadic Ea and Child Gendermentioning
confidence: 99%
“…Robinson et al (1993) reported that daughters engage in more matching of affect states than sons, so daughters were predicted to be more responsive than sons. And since daughters are less comfortable with and display lower levels of autonomy and less distance from mothers than sons (Clarke-Stewart & Hevey, 1981;Ley & Koepke, 1982;Olesker, 1984Olesker, , 1990, daughters were predicted to be more involving than sons. Given the bidirectional nature of EA (Biringen et al, 1998), parents were expected to be more sensitive to and provide more optimal structuring for daughters than sons.…”
Section: Child Gender Differencesmentioning
confidence: 99%